ANALISIS REDUPLIKASI PADA CERPEN KITA GENDONG BERGANTIAN KARYA BUDI DARMA - Ahmad Aji Fashihudin; Devi Mariyani; Sindi Quratul Uyun (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The repetition of words or word elements is called reduplication. This reduplication process is often seen in short stories. The purpose of this research is to study and explain various types of reduplication in the short story Kita Gendong Bergantian by Budi Darma. This research uses descriptive qualitative research. In this study, the data is grouped by literature research. The literature study process consists of: Data identification, which is a collection of reduplication data, then data classification, which is the presentation of data in the form of reduplication, namely complete repetition (Dwilingga), changing sound (Dwilingga copying sound), partial repetition (Dwipurwa), additive repetition, reduplication of separators (Dwimakna) and Data analysis, which is interpretation and drawing conclusions. Studies show that there are five types of reduplication. In the short story Kita Gendong Bergantian by Budi Darma, which consists of (1) full reduplication, 16 findings were found, (2) One reduplication changed the sound was found, (3) partial reduplication was found 3 findings, (4) reduplication was found as many as many as 17 findings, and (5) reduplication of the order or meaning was found as 2 findings. Of the five types of reduplication found, reduplication is the most common with the largest number.